An integrated social-ecological assessment of ecosystem service benefits in the Kagera River Basin in Eastern Africa - Khan, Ahmed S.; Hongmei Yi; Linxiu Zhang; Yu, Xiubo; Mbanzamihigo, Erasme; Umuhumuza, Gisele; Ngoga, Thierry; Yevide, Sedami Igor Armand (Regional Environmental Change, 2019)
Sustaining multiple ecosystem service benefits in transboundary river basins is a complex and challenging task in the developing world. This can be attributed to conflicting conservation and human development needs and exacerbated by climate change impacts, especially episodic drought and flooding events. We use a case study from Rwanda in the Kagera River Basin in Eastern Africa to contextualize and examine how land use cover change, water access, and agro-ecosystems are vulnerable to myriad human and natural drivers of change. An integrated framework is employed for a nested social-ecological assessment of ecosystem service benefits drawing upon landscape and vulnerability mapping, agro-commodity value chains, and institutional analyses. The conceptual framework and case study provide leverage points for vertical and horizontal linkages that include cross-sectoral partnerships, multi-level governing networks, integrated water resource management, and livelihood security. Moreover, synergy between development and conservation outcomes can be achieved through joint adaptation planning and stewardship initiatives at the local district level with full participation of resource users and community leaders. These lessons from Rwanda and the Kagera River Basin provide opportunities for mainstreaming adaptation and development planning and building resilience towards regional environmental change in Eastern Africa.